THE INTERRELATION BETWEEN THE ADEQUACY OF AVIATION TERMS TRANSLATION AND SAFETY OF FLIGHTS - Gilchenko, R.A. (Proceedings of National Aviation University (archive), 2005)
The article considers the common aspects of aerospace terminology of Ukrainian language creation. Its author determines main ways of term-formation, ways of aerospace terminology enrichment as well as some objective difficulties of the corresponding terminological system in Ukraine. The article enlightens the issue of bilinguism of Ukrainian society, and the main requirements to be met in order to decrease the language problems related accidents rate. The author gives a recommendation for development of clear and monosemantic Ukrainian aviation terminology, its standards and English-Ukrainian dictionaries.